Transcriptome analysis of eutopic endometrial stromal cells in women with adenomyosis by RNA-sequencing. Issue 5 (2nd May 2022) - Gan, Lin; Li, Yongrong; Chen, Yan; Huang, Meihua; Cao, Jian; Cao, Meiling; Wang, Zhihui; Wan, Guiping; Gui, Tao
ABSTRACT: This study aimed to identify differentially expressed genes (DEGs) and molecular pathways in eutopic endometrial stromal cells (EuESCs) from adenomyosis (AM) patients and to provide a new insight into the disease mechanisms. The gene expression profiles in adenomyotic EuESCs (A-EuESCs) and normal ESCs (N-ESCs) were analyzed by RNA-sequencing (RNA-Seq) and validated by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways enrichment analyses were performed to obtain insights into the functions of DEGs. The protein-protein interaction (PPI) network was constructed using the STRING database and visualized by Cytoscape software, and their hub genes were identified. A total of 458 up-/363 down-regulated genes were identified in A-EuESCs versus N-ESCs. The GO enrichment analysis showed that these genes were significantly enriched in calcium-dependent cell-cell adhesion. The most significant term of the KEGG pathway analysis was cytokine-cytokine receptor interaction. There were 145 nodes in the PPI network of the 157 DEGs, which were identified in significant enrichment pathway by the KEGG pathway analysis in N-ESCs and A-EuESCs. The PPI network revealed that IL-6 was a central hub gene. Besides, IL-6 was found as a central hub gene in the pro-inflammatory/chemotactic subnetwork, and EGF was noted as a central hub gene in the angiogenesis subnetwork. Our study indicated the alterations of transcriptomic profiles in A-EuESCs and provided new insights into the pathogenesis of AM. The A-EuESCs in women with AM have fundamental abnormalities that may predispose to pro-invasion/migration and angiogenesis. Graphical abstract: uf0001